2022
DOI: 10.21037/tcr-22-970
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the mutation spectrum of tissue DNA and blood ctDNA in patients with non-small cell lung cancer

Abstract: Background To study the mutations detected in tissue DNA and blood circulating tumor DNA (ctDNA) of patients with advanced lung cancer and analyze the correlations between gene mutations, clinical features, and treatment. Methods Targeted next-generation sequencing (NGS) technology based on probe hybrid capture and Illumina high-throughput sequencing was used to detect the DNA of tumor tissue samples (n=24) and blood samples (n=15) of ctDNA from 28 lung cancer patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…In addition, lung cancers frequently harbour K-RAS mutations, and it is also one of the most common origins of brain metastases [ 22 ], which could potentially explain the present finding in the tumour tissue analysed. Besides, it has been shown that K-RAS alterations found in plasma are significantly predictive of K-RAS tumour status with significant tumour and plasma status consensus [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lung cancers frequently harbour K-RAS mutations, and it is also one of the most common origins of brain metastases [ 22 ], which could potentially explain the present finding in the tumour tissue analysed. Besides, it has been shown that K-RAS alterations found in plasma are significantly predictive of K-RAS tumour status with significant tumour and plasma status consensus [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…While tissue-based NGS is currently the gold standard, plasma-based NGS is quickly becoming a routine part of clinical practice, and there are currently two FDA-approved plasma-based NGS assays commercially available ( 27 , 28 ). NGS detection of circulating tumor (cell-free) DNA (ctDNA) alterations in plasma is a relatively noninvasive method for screening high-risk populations, guiding early diagnosis and treatment, monitoring relapse, and conducting prognostic evaluation ( 29 ). NILE trial results demonstrate that the real-world impact of ctDNA-based NGS on first-line treatment choice and patient outcomes in aNSCLC begins with a significant reduction in time to treatment initiation versus tissue-based NGS ( 30 ).…”
Section: Which Sample Type To Testmentioning
confidence: 99%
“…The study confirmed that ctDNA analysis detected actionable mutations at a similar rate as tissue genotyping and similar response rates were achieved regardless of sample sources ( 30 ). However, plasma-based NGS is limited by the low abundance of ctDNA fragments in blood, which affects analytical sensitivity, with up to a 30% false-negative rate ( 4 , 29 ). ctDNA assay results can also be obstructed by clonal hematopoietic and germline alterations ( 4 , 29 ).…”
Section: Which Sample Type To Testmentioning
confidence: 99%
See 2 more Smart Citations